Advantages of Intraocular Lens Implantation in Ringer Lactate without Viscoelastic Substance in Small Incision Cataract Surgery - Pranay Singh; Ajay Prakash; Rahul P Shah; Suraj Bhagde (Delhi Journal of Ophthalmology)
Purpose: To study the advantages of using ringer lactate instead of viscoelastic substance for implantation of intraocular lens (IOL) in small incision cataract surgery (SICS). Methods: A prospective, randomized, interventional study was performed in which 100 patients of senile cataract were included. The patients were randomly divided in two groups; one in whom IOL was implanted in ringer lactate (ringer group) and other in which viscoelastic substance HydroxypropylMethylcellulose (visco group) was used for implantation of IOL. The outcome was evaluated on safety, efficacy, postoperative intraocular pressure (IOP), postoperative reaction, endothelial cell count and surgical time. Results: The mean post operative IOP at 6, 24 and 48 hrs in ringer lactate group was 16.02,13.46 and12.44 mmHg and in viscoelastic group 22.24, 17.32 and 13.84 mmHg respectively. The difference between the groups was significant (p value <0.0001). The mean post operative reaction at 24 and 48 hrs in ringer group was 1.48 and 0.72 and in visco group 1.56 and 1.08 respectively (p value < 0.0001). Regarding position of IOLs, the two groups were comparable (odds ratio: 0.32; p value >.05). The mean endothelial cell loss in visco group was 143.56 cells (6.08%), and in ringer group it was 210.68 cells (8.9%) (p= 0.055). The mean surgical time in visco group was 6.01 ± 0.93 minutes and in ringer group, the same was 5.08± 0.76 minutes (p value < 0.0001). There was no intra-operative complication in any group. Conclusion: A small modification in one step of SICS can significantly control spikes of IOP with significantly lesser post operative reaction. With some experience, implantation of IOL in the bag under a continuous irrigation of ringer lactate is safe, accurate and less time consuming method without any significant extra loss of endothelial cells.